Secreted Amyloid Precursor Protein Alpha, a Neuroprotective Protein in the Brain Has Widespread Effects on the Transcriptome and Proteome of Human Inducible Pluripotent Stem Cell-Derived Glutamatergic Neurons Related to Memory Mechanisms - Peppercorn, Katie; Kleffmann, Torsten; Jones, Owen; Hughes, Stephanie; Tate, Warren (Frontiers in Neuroscience, 2022)
Secreted amyloid precursor protein alpha (sAPP) processed from a parent human brain protein, APP, can modulate learning and memory. It has potential for development of a therapy preventing, delaying, or even reversing Alzheimer’s disease. In this study a comprehensive analysis to understand how it affects the transcriptome and proteome of the human neuron was undertaken. Human iPSC-derived glutamatergic neurons in culture were exposed to 1 nM sAPP over a time course and changes in the transcriptome and proteome were identified with RNA sequencing and SWATH-MS respectively. A large subset (~30%) of differentially expressed transcripts and proteins were functionally involved with the molecular biology of learning and memory, consistent with reported links of sAPP to memory enhancement, as well as neurogenic, neurotrophic and neuroprotective phenotypes in previous studies. Differentially expressed proteins included those encoded in previously identified Alzheimer’s risk genes, APP processing related proteins, proteins involved in synaptogenesis, neurotransmitters, receptors, synaptic vesicle proteins, cytoskeletal proteins, proteins involved in protein and organelle trafficking, and proteins important for cell signalling, transcriptional splicing, and functions of the proteosome and lysosome. We have identified a complex set of genes affected by sAPP, which may aid further investigation into the mechanism of how this neuroprotective protein affects memory formation and how it might be used as an Alzheimer’s disease therapy.